A Synchronic Cultural Approach to Modern Chinese Shame - Benjamin, Wellsand (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2022)
Ferdinand de Saussure effectively identified the way that language acts in both a diachronic and synchronic approach. The present work intends to demonstrate that de Saussure’s synchronic approach can be adequately applied to cultural constructs to enhance cultural dialogue and learning. Synchronic terms and general concepts will be applied to cultural terms and general concepts. The primary example used to develop this concept is the cultural construct of shame and its social expressions within the modern Chinese cultural context. First, Chinese culture will be established as a predominantly honor-shame culture and point to the common honor-shame aspects of patronage, kinship, purity, and tight culture. Then, specific examples of shame as it manifests itself within Chinese culture. These examples include the second-generation rich, leftover women, lying flat, and the general fear of losing face. The result is a rich and meaningful read on culture that will further dialogue and enhance cultural understanding.